Primary Breast Tuberculosis - Abdulhaleem A. Noorwali, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Primary tuberculosis of the breast is a rare disease and differential diagnosis with other benign and malignant disease of the breast can be difficult with imaging methods. Although tuberculosis is a very common disease in endemic areas, any form of tuberculosis mastitis may present with features of malignancy. Diagnosis based mainly on the identification of tubercle bacilli. A case presented of an 82-years-old woman, complaining of three lumps in right breast tail with no previous history of the disease, diagnosed as primary tuberculosis in the breast after microbiological analysis with acid-fast bacilli. It was difficult to be diagnosed and differentiated from breast cancer by radiological or histopathological tools.